2005
DOI: 10.1124/jpet.104.080408
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Bradykinin-Induced Ca2+Mobilization in Murine Proximal Tubule Epithelial Cells

Abstract: Despite the recognized physiological role of bradykinin (BK) in the kidney in maintaining glomerular and tubule function and its role in pathological states such as endotoxemia, diabetes, and other diseases, relatively little is known about the mechanisms by which BK can impact kidney function. Furthermore, the signaling of BK receptors in the murine nephron has not been fully characterized. The present studies were undertaken to examine BK-stimulated Ca 2ϩ signaling using Fura-2 in the murine proximal tubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…We demonstrated that BK causes an elevation of intracellular Ca 2+ in A498 cells, which was blocked by the BK B 2 receptor antagonist HOE-140, but not by the BK B 1 receptor antagonist des-Arg 10 -HOE-140, indicating a role for the BK B 2 receptor (Figure 2). Similar BK-induced intracellular Ca 2+ mobilization has been described in several kidney cell lines, including rat mesangial cells,29 the mIMCD-3 murine inner medullary collecting duct cell line,25 Kirsten murine sarcoma-virus transformed rat kidney KNRK cells,30 the mouse proximal tubule epithelial cell line,31 and in the human embryonic kidney (HEK293) cell line 26…”
Section: Discussionsupporting
confidence: 56%
“…We demonstrated that BK causes an elevation of intracellular Ca 2+ in A498 cells, which was blocked by the BK B 2 receptor antagonist HOE-140, but not by the BK B 1 receptor antagonist des-Arg 10 -HOE-140, indicating a role for the BK B 2 receptor (Figure 2). Similar BK-induced intracellular Ca 2+ mobilization has been described in several kidney cell lines, including rat mesangial cells,29 the mIMCD-3 murine inner medullary collecting duct cell line,25 Kirsten murine sarcoma-virus transformed rat kidney KNRK cells,30 the mouse proximal tubule epithelial cell line,31 and in the human embryonic kidney (HEK293) cell line 26…”
Section: Discussionsupporting
confidence: 56%
“…The BK B 2 receptor usually couples to the GTP-binding protein G q , and stimulates phospholipase C activity, causing phosphoinositide hydrolysis, that leads to generation of inositol triphosphate and to subsequent mobilization of intracellular Ca 2+ from the endoplasmic reticulum [22, 23]. BK-induced intracellular Ca 2+ mobilization has been described in several kidney cell lines including rat mesangial cells [24], the mIMCD-3 murine inner medullary collecting duct cell line [20], Kirsten murine sarcoma-virus transformed rat kidney KNRK cells, [25] and the TKPTS mouse proximal tubule epithelial cell line [26]. BK produced a concentration-dependent elevation of intracellular Ca 2+ in HEK293 cells (Figure 2) with a EC 50 value of 36.5 ± 8.0 10 −9 M which is somewhat higher than EC 50 values reported for other renal cell lines that demonstrate nanomolar potency of BK for stimulating Ca 2+ mobilization [20,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…BK-induced intracellular Ca 2+ mobilization has been described in several kidney cell lines including rat mesangial cells [24], the mIMCD-3 murine inner medullary collecting duct cell line [20], Kirsten murine sarcoma-virus transformed rat kidney KNRK cells, [25] and the TKPTS mouse proximal tubule epithelial cell line [26]. BK produced a concentration-dependent elevation of intracellular Ca 2+ in HEK293 cells (Figure 2) with a EC 50 value of 36.5 ± 8.0 10 −9 M which is somewhat higher than EC 50 values reported for other renal cell lines that demonstrate nanomolar potency of BK for stimulating Ca 2+ mobilization [20,24,25,26]. Intracellular Ca 2+ mobilization was completely blocked by the specific phospholipase C (PLC) inhibitor, U-73122 supporting the requirement for PLC activation in the BK-induced Ca 2+ signal.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that B 2 receptors couple with the Gq protein. Activation of the Gq protein activates phospholipase C, which induces a number of intracellular second messenger systems, including 1, 2-diacylglycerol and inositol 1, 4, 5-trisphosphate, which activates protein kinase C and mobilizes intracellular Ca 2+ , respectively (Walker et al, 1995; Tiwari et al, 2005). …”
Section: Introductionmentioning
confidence: 99%